-3(b + 9) = -9
First, divide both sides by -3. / Your problem should look like: b + 9 = [tex] \frac{-9}{-3} [/tex]
Second, simplify [tex] \frac{9}{-3} [/tex] to [tex] \frac{9}{3} [/tex] / Your problem should look like: b + 9 = [tex] \frac{9}{3} [/tex]
Third, simplify [tex] \frac{9}{3} [/tex] to 3. / Your problem should look like: b + 9 = 3
Fourth, subtract 9 from both sides. / Your problem should look like: b = 3 - 9
Fifth, simplify 3 - 9 to get -6. / Your problem should look like: b = -6
Answer: b = -6